Assessing Site Waste Management Practices And Cost Between Conventional and Industrialised Building System (IBS) Projects in Malaysia - Abd Shukor, Ani Saifuza; Idris, Nor Hanisah; Bakri, Anis Sazira (International Journal of Sustainable Construction Engineering and Technology, 2022)
The Urban development and demands in the construction industry and the increasing population numbers have positively contributed to the rising waste generation. The growth and expansion of construction activities enhanced the problem of waste generation on construction sites. In the Malaysian construction industry, there is a pressing issue of minimising construction waste, which causes significant impacts on the environment. Malaysia is moving towards better construction waste management; however, there is still insufficient collection and improper construction waste disposal in projects site. Practices to reduce, reuse, or recycle waste have not yet achieved widespread implementation due to the cost incurred in handling and transporting the physical waste to the dumpsite. Thus, adopting an Industrialised Building System (IBS) has been one alternative to the conventional construction method to reduce construction waste. The research aim is to compare site waste management practices between conventional and IBS projects. The research examines the types of site waste generated from construction project activities, the types of site waste management practices, and the cost involved in managing site waste. The research methodology used qualitative research and used a case study approach. The data is gained from semi- structured interviews with conventional and IBS contractors in Malaysia. The analysis is based on cross-case analysis and pattern matching. Findings from semi-structured interviews based on six comparative case studies revealed that there are some differences between the types of site waste generate by the conventional and IBS projects due to some causes such as improper storage and wrong handling material. Adopting an IBS can greatly minimize construction waste, saving the cost of materials, and improve the environmental performance for overall site conditions. This research shows that the government should play an important role by encourage all the construction company to implement IBS as the new way in minimizing the construction waste.